Cultural Policy Evaluation: Benchmarking Stakeholders’ Preferences Using The Analytic Hierarchy Process Technique - Del Barrio Tellado, María José; Espinosa Casero, Fátima; Gómez Zapata, Jonathan Daniel (Ekonomiaz, 2025)
Participatory management models of cultural institutions are gaining increasing interest but have so far been subject to little evaluation. The aim of this paper is to estimate the value allocated to the participatory policies of a sample of museums from the institutional perspective (managers and stakeholders) through benchmarking dimensions and options proposed in the cultural strategy. We apply the analytic hierarchy process method, which allows us to obtain a robust hierarchical ranking of alternatives according to stakeholder preference intensity. Results show a priority for social and technological innovation strategies and less interest in co-governance actions. This research represents a proposal for an efficient evaluation of cultural policies and the performance of cultural institutions.